2022
DOI: 10.1158/2159-8290.cd-22-0424
|View full text |Cite
|
Sign up to set email alerts
|

Mutant NPM1 Hijacks Transcriptional Hubs to Maintain Pathogenic Gene Programs in Acute Myeloid Leukemia

Abstract: Nucleophosmin (NPM1) is a ubiquitously expressed nucleolar protein with a wide range of biological functions. In 30% of acute myeloid leukemia (AML), the terminal exon of NPM1 is often found mutated, resulting in the addition of a nuclear export signal and a shift of the protein to the cytoplasm (NPM1c). AMLs carrying this mutation have aberrant expression of the HOXA/B genes, whose overexpression lead to leukemogenic transformation. Here, for the first time, we comprehensively prove NPM1c binds to a subset of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 61 publications
(45 reference statements)
0
34
0
Order By: Relevance
“…Regardless of this dissimilarity, which could be secondary to differences in the experimental procedures and bioinformatic analysis, both studies clearly show that NPM1c is recruited at HOX/MEIS and directly regulates the transcription of these critical targets. Indeed, NPM1c was found enriched at active chromatin sites, together with activating histone marks, MLL1 and RNA Polymerase II (Pol II) and specific degradation of NPM1c resulted in immediate halt of HOX/MEIS transcription (within 15 min) secondary to the loss of Pol II from these loci 13,14 . Furthermore, pharmacologic MLL‐Menin inhibition induced the loss of NPM1c from several of its chromatin targets, including MEIS1 , followed by their downregulation 13 …”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Regardless of this dissimilarity, which could be secondary to differences in the experimental procedures and bioinformatic analysis, both studies clearly show that NPM1c is recruited at HOX/MEIS and directly regulates the transcription of these critical targets. Indeed, NPM1c was found enriched at active chromatin sites, together with activating histone marks, MLL1 and RNA Polymerase II (Pol II) and specific degradation of NPM1c resulted in immediate halt of HOX/MEIS transcription (within 15 min) secondary to the loss of Pol II from these loci 13,14 . Furthermore, pharmacologic MLL‐Menin inhibition induced the loss of NPM1c from several of its chromatin targets, including MEIS1 , followed by their downregulation 13 …”
Section: Figurementioning
confidence: 99%
“…In addition to XPO1, Uckelmann et al 13 demonstrated that one of the two NPM1 acidic domains (~aa 120 to 150) is also necessary for an efficient NPM1c recruitment to chromatin. Wang et al 14 proposed that the generation of NPM1c phase separated nuclear condensates is critical for the recruitment of NPM1c to chromatin and to hijack the transcriptional machinery at its target loci. Whether NPM1c condensates are actually necessary for HOX/MEIS expression and whether the acidic domain is involved in the process of phase separation process itself remains to be clarified.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Although homeobox gene deregulation is strongly linked with many human malignancies, IRX family has not yet been fully functionally explored (8,14,15). The IRX family includes six genes, IRX1, IRX2, and IRX4 (IRX cluster A) which are located in chromosome 5 and IRX3, IRX5, and IRX6 (IRX cluster B) which are located in chromosome 16 (13,16).…”
Section: Introductionmentioning
confidence: 99%